PEMBUATAN PROGRAM APLIKASI SISTEM INVENTORI BERBASIS VISUAL BASIC PADA SINAR BARU - Dessy Dessy; Ery Dewayani (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Application system inventory program based on visual basic on Sinar Baru for helping admin to manage in or out items systematically which it doesn’t save and computerized well. The programming using System Development Life Cicle (SDLC). SDLC has four phases, that are: Planning Phase, Analysis Phase, Design Phase, and Implementation Phase. Another design that used for this program are flowchart, Context diagram, data flow diagram (DFD), Entity Relation Diagram (ERD), Relational Table .Visual Basic as programming language and SQL Management Server as database. The result of this application are recording about in or out items, sales return and purchasing return can be save and computerized systematically.